Changes in Work-Family Conflict of Chinese Employees: A Cross-Temporal Meta-Analysis, 2005–2016 - Xin, Sufei; Zheng, Yang; Xin, Ziqiang (Frontiers in Psychology, 2020)
With the rapid growth of China’s economy, work-family conflict (WFC) levels of Chinese employees might have changed over time. The present research performed a cross-temporal meta-analysis of 71 papers using the Work-Family Conflict Scale (WFCS) to investigate changes in Chinese employees’ WFC (N = 23,635) from 2005 to 2016. Results showed that the WFC level of employees increased significantly by 0.77 standard deviations over the past 12 years. The increasing trend across birth cohorts occurred among both male and female employees, which is slightly more salient among male employees. However, there was no significant gender difference in WFC scores. The increase in WFC scores among Chinese employees was associated with certain social indicators (divorce rate, residents’ consumption level, elderly dependency ratio, family size, number of employees and number of college graduates) of 5 years before and the year of data collection, which indicates that social changes played an important role in changes of WFC.